New Optics in Analysis and Work Estimation of Abroad Romanian Citizens - Nita Dobrota (Theoretical and Applied Economics, 2006)
Management of the active population employment became more and more complex in each country in a knowledge based society and a new economy, which are in a high connection with globalization and integration processes. From this point of view, the departures to work abroad, legal or illegal of the Romanian citizens for a better payment have already generated social-economic effects which have to concern more our public authorities. In this study we try to show the necessity of a national strategy for a full and efficient employment of whole Romanian labour potential, lay emphasis on the active population. In the same time through the indicators based on theoretical-methodological analyses and empiric estimated, we suggest some possible coordinates of this strategy.